1983
DOI: 10.1111/j.1399-3054.1983.tb00896.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultraviolet‐B irradiation on plants during mild water stress.

Abstract: Cucumber (Cucumis sativus L. cv. Delikatess) and radish (Raphanus sativus L. cv. Saxa Treib) were grown in a factorial design under two ultraviolet‐B (UV–B) irradiances and three levels of water stress. On a weighted, daily dose basis the UV–B radiation treatments were equivalent to ambient levels during the beginning of the growing season (controls) and those predicted for an 11.6% ozone depletion during the summer solstice at 49°N latitude. Water stress was achieved by varying the frequency of watering. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(32 citation statements)
references
References 14 publications
1
30
1
Order By: Relevance
“…Tevini et al 20,21) reported that the water stress caused decreases in the fresh weights and leaf areas in cucumber seedlings. Similar observations were also reported by Yang et al 22) In our results, the fresh weights of leaves in the cucumber seedlings greatly decreased due to the water stress that was added to the stress of the strong light radiation (Table 1), which is consistent with the results from these previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Tevini et al 20,21) reported that the water stress caused decreases in the fresh weights and leaf areas in cucumber seedlings. Similar observations were also reported by Yang et al 22) In our results, the fresh weights of leaves in the cucumber seedlings greatly decreased due to the water stress that was added to the stress of the strong light radiation (Table 1), which is consistent with the results from these previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have employed UV-B doses equivalent to less than a 20% reduction in the ozone layer. Nevertheless, these studies have also demonstrated the deleterious effects of UV-B irradiation upon plants (24)(25)(26)(27).…”
Section: Abstracimentioning
confidence: 99%
“…Only a few studies have employed UV-B doses equivalent to less than a 20% reduction in the ozone layer. Nevertheless, these studies have also demonstrated the deleterious effects of UV-B irradiation upon plants (24)(25)(26)(27).In addition to unrealistically high UV-B irradiances, another criticism of many previous UV-B studies has been the low PPFD under which the plants were grown and irradiated. Only a few studies have examined the effects of UV-B radiation on plants grown under relatively high PPFDs, which more approximate natural conditions (24, 25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A modulated fluorimeter (PAM-2000, Walz, Germany) was used to estimate ∮PSII simultaneously with Asa t, and Fv/Fm was measured after 30 min dark-adaptation (Damian et al, 1998). 일부 연구결과에 따르면 UV-B 조사에 의해 기공전도도가 감소하는 것이 밝혀졌다 (Teramura et al, 1983;Negash, 1987;Dai et al, 1992;Middleton and Teramura, 1993). (Murali and Teramua, 1986;Sullivan and Teramura, 1989;Teramura et al, 1991;Ziska and Teramura, 1992;Middleton and Teramura, 1993;Damian et al, 1998).…”
Section: Figmentioning
confidence: 99%